2015
DOI: 10.1021/acschembio.5b00767
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Taxadiene Epoxidation by Taxadiene-5α-Hydroxylase

Abstract: The anticancer molecule taxol (Paclitaxel) stands as one of the most medically and economically important natural products. However, despite decades of extensive study, its biosynthesis remains poorly understood. Unpredictable behavior of the first oxygenation enzyme, taxadiene-5α-hydroxylase, which produces a range of undesired products, currently stands as a key bottleneck to improved taxol production. We herein present chemical and biological evidence of an unreported epoxidase activity of taxadiene-5α-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 33 publications
12
78
1
Order By: Relevance
“…Cell density was monitored by UV/Vis spectroscopy at 600 nm while glucose consumption was determined by HPLC using an Aminex HPX-87H column (300 × 7.8 mm) (Bio-Rad) on an Infinity 1260 series HPLC (Agilent) at a flow rate of 0.7 mL/min with 14 mM H 2 SO 4 , at room temperature using a refractive index detector set at 50°C. C18 flash resin was added to taxadiene bioreactors to capture taxadiene and eluted in acetonitrile for purification by semipreparative HPLC as previously described (33).…”
mentioning
confidence: 99%
“…Cell density was monitored by UV/Vis spectroscopy at 600 nm while glucose consumption was determined by HPLC using an Aminex HPX-87H column (300 × 7.8 mm) (Bio-Rad) on an Infinity 1260 series HPLC (Agilent) at a flow rate of 0.7 mL/min with 14 mM H 2 SO 4 , at room temperature using a refractive index detector set at 50°C. C18 flash resin was added to taxadiene bioreactors to capture taxadiene and eluted in acetonitrile for purification by semipreparative HPLC as previously described (33).…”
mentioning
confidence: 99%
“…Based on the prevalent distribution of the pattern of hydroxylation, the next predicted step requires the P450 taxadiene-5α-hydroxylase, CYP725A4, which catalyzes the regio-selective hydroxylation of the 5α position of taxadiene to yield taxa-4(20),11(12)-dien-5α-ol (T5OH/T-5α-ol) (Fig. 10 , Biggs et al 2016b ; Edgar et al 2016 ; Hefner et al 1996 ; Jennewein et al 2004 ). The subsequent conversions include a series of P450-mediated oxygenations, providing the molecular handles for acylations and further conjugation of the skeleton.…”
Section: Oxidation Of Labdane-type and Macrocyclic Diterpenesmentioning
confidence: 99%
“…It has been observed that the heterologous expression of taxadiene synthase and CYP725A4 in tobacco ( Nicotiana sylvestris ) result in the formation of 5(12)-oxa-3(11)-cyclotaxane (OCT) instead of T5OH (Rontein et al 2008 ). Further studies described that expression of recombinant taxadiene synthase and CYP725A4 in an E. coli host leads to equal formation of T5OH and OCT and indicated that the lack of specificity of the oxygenation represents a first limitation to overcome (Ajikumar et al 2010 ; Edgar et al 2016 ; Zhou et al 2015 ). Investigating the mechanism more in detail, earlier studies have suggested that promiscuous H-atom abstraction from both the isomeric olefinic precursors, taxa-4(5),11(2)-diene and taxa-4(20),11(2)-diene, forming an allylic radical followed by oxygen insertion can lead to the formation of T5OH (Hefner et al 1996 ; Jennewein et al 2004 ).…”
Section: Oxidation Of Labdane-type and Macrocyclic Diterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Yadav studied a CYP725A4 construct and found that CYP725A4 acts on 4 substrates to form 12 products, and that taxadiene-5α-ol was only a very minor product [13]. Additionally, other groups have suggested the presence of an epoxide intermediate in the conversion of taxadiene to taxadiene-5α-ol [14, 15]. In order to help resolve the ambiguity surrounding CYP725A4-mediated taxadiene hydroxylation, we conducted a study comparing the product distribution of different CYP725A4 constructs that are purified via E. coli fermentation [16].…”
Section: Introductionmentioning
confidence: 99%